An Olive Agenda for Putting Economic and Ecological Justice at the Heart of Faith - Jong, Thandi Soko-de (My University, 2023)
This paper focuses on an “olive agenda” for putting economic and ecological justice at the heart of faith. For many communities in Southern Africa, nature is defined as “that which is created” and “everything in it, is the environment”. This perspective contrasts with many of the lived realities today, where nature is seen less as being summed up in God’s creation and sustenance and is instead regarded more as something to be consumed and used for its benefits. This paper draws from Ekari Mbvundula’s Montague’s Last to argue for economic and ecological justice in dialogue with Steve De Gruchy’s notion of an olive agenda to argue for sustainable, economic and ecological justice.
Keywords: Olive Agenda; Economic Justice; Ecological Justice